Morphology of the preadult stages of Coronaproctus castanopsis Li, Xu & Wu (Hemiptera: Coccomorpha: Monophlebidae) - Zheng, Xinyi; Li, Jiani; Wu, San’an (Zootaxa, 2023)
All the preadult stages of Coronaproctus castanopsis Li, Xu & Wu, 2023 are described and illustrated (first- and second-instar nymphs, third-instar male and female nymphs, and the male pupa), based on material from Zhejiang Province, China. A key to separate the developmental stages is provided.